2022
DOI: 10.1111/jopr.13516
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Different Attachment Systems for Digitally Designed Mandibular Implant Overdenture

Abstract: Purpose: Primary retention and gradual loss of retention of different attachment systems are important key factors in proper attachment selection; however, studies on attachment retention show a wide range of retention values concerning the same attachment system. This in vitro study uses a novel approach that utilizes a digitally designed and 3D-printed reinforced overdenture, which has a digitally determined geometric center, in order to standardize results for future research and clinical work. This study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…In comparable studies, the number of cycles performed ranges from 3000 to 30,000. [14][15][16][17][18][19][20][21][22][23] The sample size of 10 specimens for each test series is consistent with other studies even though there is no clear consensus. 14,16,17,22,24 In this study, the manufacturer's specifications could only be confirmed for the initial retention force of green Novaloc retention inserts on a Novaloc abutment (Ng-N) and for the white Novaloc retention inserts on a Novaloc abutment (Nw-N) as well as the green Novaloc retention inserts on a Locator abutment (Ng-L) after 10,000 cycles.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In comparable studies, the number of cycles performed ranges from 3000 to 30,000. [14][15][16][17][18][19][20][21][22][23] The sample size of 10 specimens for each test series is consistent with other studies even though there is no clear consensus. 14,16,17,22,24 In this study, the manufacturer's specifications could only be confirmed for the initial retention force of green Novaloc retention inserts on a Novaloc abutment (Ng-N) and for the white Novaloc retention inserts on a Novaloc abutment (Nw-N) as well as the green Novaloc retention inserts on a Locator abutment (Ng-L) after 10,000 cycles.…”
Section: Discussionsupporting
confidence: 76%
“…Current research indicates that the followup Locator R-Tx system may have a more stable retention pattern. 21 The simulation of mastication only seems to cause less wear of the legacy Locator inserts, as much lower retention losses were observed. 24 For Novaloc retention inserts, there are only a few publications with varying results.…”
Section: Discussionmentioning
confidence: 97%
“…Takeda et al 6 reported using 3D printing technology for denture duplication. Application of Crea‐lign gum material was done to mimic the natural gingival pink color and appearance 19 . The 3D printed supporting arms are only placed on the polished denture surface, as placing the supporting arms on the intaglio surface will affect future denture adaptation and retention in the patient's mouth 2 …”
Section: Discussionmentioning
confidence: 99%
“…Application of Crea-lign gum material was done to mimic the natural gingival pink color and appearance. 19 The 3D printed supporting arms are only placed on the polished denture surface, as placing the supporting arms on the intaglio surface will affect future denture adaptation and retention in the patient's mouth. 2 This denture replication technique may be indicated when patients are very comfortable with their existing dentures and would like a backup replicate with some modifications, such as denture relining, to use as a spare denture.…”
Section: Introductionmentioning
confidence: 99%
“…The sample size was calculated using G Power version 3.1.9.2. and according to previous studies [ 8 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%